Exchange Rate and Turkish Tourism Trade - Citak, Ferhat (International Journal of Economics and Financial Issues, 2018)
The aim of this paper is to analyze the relationship between the exchange rate and tourism trade in Turkey from 1970 to 2016 by applying three Vector autoregression (VAR) models. The main findings of this paper can be documented as follows: (i) there is no long-run cointegration relationship among the variables (ii) the reaction of the export revenue to an unexpected 1% depreciation exchange rate shock is positive and statistically significant at the 95% level (iii) import tourism spending exhibits a robust significant positive response to home demand shock (iv) the response of trade balance to 1% shock in the exchange rate is negative and significant, which shows the evidence of J-curve behavior for the selected eight European countries. Keywords: Trade balance, Turkish tourism, J-curve, Cointegration, Vector autoregression JEL Classification: E21